MEREDAM RASA INSECURITY DALAM KARYA POTRAIT FOTOGRAFI BERJUDUL CANTIK TIDAK HANYA DARI FISIK - Perdana, Ahmad Zakhi Danang; Endriawan, Didit; Kusumanugraha, Sigit (eProceedings of Art & Design, 2023)
Insecure is a feeling of insecurity where an individual feels insecure and anxious about something. At  this  time people often mention  the word  insecure when  they  see  someone  more  beautiful  than  themselves.  everyone  who  has feelings of insecurity can vary. The causes of insecurity can come from events that cause trauma, past experiences, social conditions, to the surrounding environment. Insecurity  is a condition that should not be ignored, because  it can be related to the condition of the body as a whole, it can even reduce a person's quality of life. Therefore,  the author would  like  to convey  in  the work of  the  Final Project  that beauty is not only from the physical in the form of the work. Therefore, the author made a work entitled "Reduce the feeling of insecurity in potrait photography work entitled Beauty, Not Only  From the  Physical".  The purpose of making  this  Final Project is to visualize the insecurity of a woman through the media of photography. The end result is that the author will make a photo album that aims to relieve the insecurity of any woman who reads and sees the work of this Final Project. Keywords: insecurity, beauty, photography, woman, album photo